2017
DOI: 10.2174/0929867324666170424124416
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic Potential of Animal β-hairpin Antimicrobial Peptides

Abstract: Endogenous antimicrobial peptides (AMPs) are evolutionary ancient molecular factors of innate immunity that play the key role in host defense. Because of the low resistance rate, AMPs have caught extensive attention as possible alternatives to conventional antibiotics. Over the last years, it has become evident that biological functions of AMPs are beyond direct killing of microbial cells. This review focuses on a relatively small family of animal host defense peptides with the β-hairpin structure stabilized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The two disulfide-enclosed loops of Ate1a differ substantially in length, with loop 1 containing just two residues compared to five in loop 3. In combination with the two prolines in loop 3, this asymmetry prevents the formation of secondary structures characteristic of other disulfide-enclosed hairpin-like structures such as b-hairpin antimicrobial peptides (AMPs) [40] (Fig. 4b) or the cystine-stabilised a/a (CSaa) fold [41] (Fig.…”
Section: Ate1a Defines a New Peptide Foldmentioning
confidence: 99%
“…The two disulfide-enclosed loops of Ate1a differ substantially in length, with loop 1 containing just two residues compared to five in loop 3. In combination with the two prolines in loop 3, this asymmetry prevents the formation of secondary structures characteristic of other disulfide-enclosed hairpin-like structures such as b-hairpin antimicrobial peptides (AMPs) [40] (Fig. 4b) or the cystine-stabilised a/a (CSaa) fold [41] (Fig.…”
Section: Ate1a Defines a New Peptide Foldmentioning
confidence: 99%
“…Some antimicrobial peptides are also considered as putative anticancer agents [4,5,6]. Previous studies demonstrated that β-hairpin cationic antimicrobial peptides, for example, tachyplesin I from horseshoe crab hemocytes, gomesin from spider hemocytes, and protegrin-1 from porcine leukocytes displayed both antibacterial and antitumor activities [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…While these non-natural, linear sequences can be engineered to attack bacterial pathogens, nature appears to prefer cyclic peptide building blocks to construct supramolecular antimicrobials. Exemplifying this are polyphemusin-1 (PM-1) [76][77][78][79] found in horseshoe crab hemocytes, θ-defensin BTD-2 [79][80][81] isolated from baboons and protegrin-1 and -4 (PG-1, -4) [78,79,[82][83][84][85] derived from porcine leukocytes, which all adopt cyclic conformations and β-sheet rich amyloid assemblies that potentiate their antimicrobial activity. PM-1, for instance, displays nanomolar activity towards E. coli (MIC = 30 nM), with broad spectrum effects towards a multitude of other pathogens [76][77][78][79].…”
Section: β-Amyloid Fibrilsmentioning
confidence: 99%
“…This suggests that the combinatorial assembly of diverse amyloid-forming peptides could access more structurally stable and potent antimicrobial states compared to homogenous systems. Similarly, protegrin peptides PG-1 and PG-4 display conformationally-dependent, broad-spectrum activity [78,79,82,83], which is potentiated upon oligomerization into β-sheet rich amyloid assembles [84,85]. To demonstrate this, Guor et al tested the activity of monomeric and self-assembled PG-4 against B. subtilis to elucidate gain-or loss-of function after higher order assembly [84].…”
Section: β-Amyloid Fibrilsmentioning
confidence: 99%